Formation control for car-like mobile robots using front-wheel driving and steering. (25th May 2018) - Chen, Haojie; Yang, Hong'an; Wang, Xu; Zhang, Ting
To solve the problem of front wheels being jammed due to the passive trajectory tracking of the conventional car-like robot in the leader–follower formation control, we propose a novel car-like robot with the integration of front-wheel driving and steering. We establish its kinematic model, then analyze its controllability via the method of chained form system, and design the trajectory-tracking controller via the backstepping method. Simulations and experimental results validate our algorithm. This novel car-like robot with the integration of front-wheel driving and steering system not only avoids the jamming in the formation motion, but also owes the advantages of compacter structure, lighter body, and lower energy consumption.